PDGF-mediated autophagy regulates vascular smooth muscle cell phenotype and resistance to oxidative stress - Salabei, Joshua K; Cummins, Timothy D; Singh, Mahavir; Jones, Steven P; Bhatnagar, Aruni; Hill, Bradford G (Biochemical journal, 2013)
Vascular injury and chronic arterial diseases result in exposure of VSMCs (vascular smooth muscle cells) to increased concentrations of growth factors. The mechanisms by which growth factors trigger VSMC phenotype transitions remain unclear. Because cellular reprogramming initiated by growth factors requires not only the induction of genes involved in cell proliferation, but also the removal of contractile proteins, we hypothesized that autophagy is an essential modulator of VSMC phenotype. Treatment of VSMCs with PDGF (platelet-derived growth factor)-BB resulted in decreased expression of the contractile phenotype markers calponin and α-smooth muscle actin and up-regulation of the synthetic phenotype markers osteopontin and vimentin. Autophagy, as assessed by LC3 (microtubule-associated protein light chain 3 α; also known as MAP1LC3A)-II abundance, LC3 puncta formation and electron microscopy, was activated by PDGF exposure. Inhibition of autophagy with 3-methyladenine, spautin-1 or bafilomycin stabilized the contractile phenotype. In particular, spautin-1 stabilized α-smooth muscle cell actin and calponin in PDGF-treated cells and prevented actin filament disorganization, diminished production of extracellular matrix, and abrogated VSMC hyperproliferation and migration. Treatment of cells with PDGF prevented protein damage and cell death caused by exposure to the lipid peroxidation product 4-hydroxynonenal. The results of the present study demonstrate a distinct form of autophagy induced by PDGF that is essential for attaining the synthetic phenotype and for survival under the conditions of high oxidative stress found to occur in vascular lesions.